Inovação verde, capacidades dinâmicas e competitividade: um estudo em empresas internacionalizadas situadas em Uberlândia-MG e Ribeirão Preto-SP - Ferreira, Giselle Fernandes (2025)
i) Contextualization: The need for organizations to maintain their competitiveness in the current context goes beyond purely economic considerations, highlighting the need for a holistic approach that also encompasses social and environmental dimensions. In alignment with the UN Sustainable Development Goals (SDGs) established in 2015, green innovation and dynamic capabilities are identified as key elements for sustainable development and promoting competitive advantages in businesses. ii) Objective: The study aims to analyze whether dynamic capabilities promote green innovation and generate competitive advantages in internationalized companies in Uberlândia-MG and Ribeirão Preto-MG. iii) Method: The research adopted a quantitative approach, with data collected through a questionnaire applied to 122 exporting companies between 2019 and 2021. The analysis was conducted using the SmartPLS 4.0 software, employing Structural Equation Modeling with the Partial Least Squares (PLS-PM) method to test the research model hypotheses. iv) Results: The results show that technological capabilities are strongly associated with green innovation, both in products and processes. Companies with higher technological development demonstrated a greater ability to meet sustainability demands in the international market, promoting more efficient and environmentally responsible operations. Organizational and environmental capabilities were crucial for green process innovation, strengthening sustainable management and organizational practices. However, green process innovation did not generate significant competitive advantages or expected benefits for the companies, although it contributed to sustainability and organizational reputation. The green innovation behavior of the companies revealed a positive influence on achieving expected benefits, reinforcing that sustainable practices can generate economic and social value in the global market. v) Alignment of the research with the PPGAdm area of concentration (Regionality and Management) and research line: The research fits into the Regionality and Management area by investigating how dynamic capabilities and green innovation impact the competitiveness of regional companies, connecting local and global aspects. Focusing on exporting companies in Uberlândia and Ribeirão Preto, it addresses management practices that promote sustainability and strengthen regional and international economic relationships. vi) Impact and innovative character in intellectual production: Theoretically, the research expands the understanding of the relationship between sustainability, technology, and competitiveness, with an innovative character by integrating sustainable practices related to dynamic capabilities in underexplored regional contexts. vii) Economic, social, and regional impact: The research offers practical contributions, such as guidelines for managers to adopt green innovation strategies, promoting operational efficiency and social, economic, and regional impacts. It also reinforces the role of Uberlândia and Ribeirão Preto as economic and commercial hubs, strengthening local economies, generating jobs, and integrating international markets. viii) Regional implications: The findings provide support for companies in these regions to improve their competitiveness and sustainability, promoting economic growth and consolidating their global relevance through green innovation practices. ix) Sustainable Development Goals addressed in the research: The research fosters integrated and sustainable economic, social, and environmental development by proposing strategies that promote green innovation and partnerships between companies and stakeholders, addressing SDG 8, SDG 9, and SDG 17.